Exploring the associations between work addiction, emotional intelligence, psychological detachment, and interpersonal conflicts in young employees - Jiafan Sheng; Gao Zheng; Huilin Wang; Ziqing Xu (Frontiers in Public Health, 2025)
IntroductionWork addiction is a growing concern in modern workplaces, particularly among young employees who face intense competition, high performance expectations, and limited work experience. These challenges not only strain their emotional intelligence and psychological detachment but also intensify interpersonal conflicts, negatively impacting workplace dynamics and well-being. This study explores the associations between work addiction, emotional intelligence, psychological detachment, and interpersonal conflicts, providing a deeper understanding of these interconnected factors among young employees.MethodsThis study used a questionnaire survey to collect data from young employees aged 18 to 35 in southern China. The research employed convenience sampling and snowball sampling methods, with 362 valid responses collected. SmartPLS software was used for modeling analysis to verify the hypothesized paths, and bootstrapping with 5,000 samples was applied to test the indirect effects.ResultsThe results indicated that all hypotheses were supported. Work addiction was negatively associated with emotional intelligence and psychological detachment, while emotional intelligence was positively associated with psychological detachment. Emotional intelligence and psychological detachment were both negatively associated with interpersonal conflicts. Furthermore, emotional intelligence and psychological detachment were found to mediate the relationship between work addiction and interpersonal conflicts.DiscussionThe findings highlight the need for organizations to address work addiction by promoting a healthier work culture and supporting employees’ emotional and psychological well-being. Encouraging strategies that enhance emotional intelligence and psychological detachment can help mitigate workplace conflicts and improve overall employee relationships.